Analysis of the Relationship between Individual Taxpayer Compliance Viewed from Type of Work, Income Level, and Tax Digitalization - Ningsih, Triana Zara; Handayani Z, Desi; Gustati, Gustati (FEB Universitas Sultan Ageng Tirtayasa, 2024)
This study aims to look at the relationship between the type of job, income level, and tax digitization with individual taxpayer compliance. This study is a quantitative research that uses questionnaires as data collection instruments. The population in this study is individual taxpayers registered with several KPPs in Indonesia with a total of 162 respondents. The data were analyzed using the chi square test and contingency coefficient supported by frequency and crosstab. The results of this study prove that there is a positive and significant correlation between the type of work, namely employees and self-employed, and taxpayer compliance. In addition, there is a positive and significant correlation between income levels, both income less than PTKP and income more than PTKP, and taxpayer compliance. A positive and significant correlation was also found between the perception of tax digitization and taxpayer compliance. It is hoped that this study can provide insight into the factors that affect the compliance of individual taxpayers and produce recommendations for tax institutions to improve policies through the type of work, income level, and utilization of digitalization.